Carbon-catalyzed oxygen-mediated dehydrogenation of formaldehyde in alkaline solution for efficient hydrogen production. (30th July 2022) - Lu, Nan; Yan, Xiaoqing; Tan, Hui Ling; Kobayashi, Hisayoshi; Yu, Xuehan; Li, Yuezhou; Zhang, Jiemei; Peng, Zhengxin; Sui, Jing; Zhang, Ziying; Liu, Wen; Li, Renhong; et al.
Abstract: We report an efficient process to dehydrogenate formaldehyde in alkaline solution, catalyzed by carbon nanotubes (CNTs) via a unique reaction mechanism involving molecular O2 . The superior catalytic performance of carbon nanotubes (CNTs) compared to the other carbon-based catalysts is attributed to their sp 2 -carbon-rich surface, hydrophilicity and abundant surface defects, which are the most plausible active sites. Peroxide species originating from the activation of adsorbed molecular oxygen on the CNTs is found to be a key to C–H activation, leading to efficient hydrogen production. The cost-effective carbon-based dehydrogenation catalysts offer new opportunities to the development of novel liquid organic hydrogen carrier technologies. Graphical abstract: Image 1 Highlights: Mediated by O2, carbon materials can act as catalysts for dehydrogenation. Delocalized π electrons and hydrophilicity are key to carbon materials as catalysts. Carbon nanotubes have excellent catalytic dehydrogenation performance. Defects on the surface are identified as the catalytic site. The specific catalytic dehydrogenation mechanism is elaborated.